2013
DOI: 10.1364/oe.21.017372
|View full text |Cite
|
Sign up to set email alerts
|

Study of EDFA and Raman system transmission reach with 256 Gb/s PM-16QAM signals over three optical fibers with 100 km spans

Abstract: We compare the transmission performance of three different optical fibers in separate 256 Gb/s PM-16QAM systems amplified with erbium doped fiber amplifiers (EDFAs) and distributed Raman amplification. The span length in each system is 100 km. The fibers studied include standard single-mode fiber, single-mode fiber with ultra-low loss, and ultra-low loss fiber with large effective area. We find that the single-mode fiber with ultra-low loss and the large effective area fiber with ultra-low loss afford reach ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…A similar method was shown by Papernyi et al [6], where the authors demonstrated cascaded sixth-order distributed Raman amplification using several FBGs, improving the receiver's sensitivity by 10 dB. These methods are proven advantageous in 2 of 9 comparison with systems based only on erbium-doped fiber amplifier (EDFA) [7][8][9] in both long-haul and unrepeatered transmission systems.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…A similar method was shown by Papernyi et al [6], where the authors demonstrated cascaded sixth-order distributed Raman amplification using several FBGs, improving the receiver's sensitivity by 10 dB. These methods are proven advantageous in 2 of 9 comparison with systems based only on erbium-doped fiber amplifier (EDFA) [7][8][9] in both long-haul and unrepeatered transmission systems.…”
Section: Introductionmentioning
confidence: 75%
“…Papernyi et al [6], where the authors demonstrated cascaded sixth-order distributed Raman amplification using several FBGs, improving the receiver's sensitivity by 10 dB. These methods are proven advantageous in comparison with systems based only on erbium-doped fiber amplifier (EDFA) [7][8][9] in both long-haul and unrepeatered transmission systems. In this paper, we experimentally investigate the performance of a single-channel 28-GBaud 64-QAM transmission with coherent detection over different Raman amplification schemes and confirm the results with numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Distributed Raman amplification 1 (DRA) reduces signal decay in the fibre span leading to a higher OSNR which can allow longer reach in long-haul transmission 2,3 or longer total distance in unrepeatered systems 4,5 . Ultra-long Raman fibre laser (URFL) 6 based amplification can further reduce the signal power variation in the fibre and has proved advantageous in comparison with EDFA only based systems 7 . In this paper, we experimentally investigate the performances of a single channel 28GBaud 64-QAM transmission with coherent detection over different Raman amplification schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Low noise distributed Raman amplification is now a well-established method that can overcome the limits set by EDFA and satisfy the bandwidth demand. In both long-haul [3,4] and unrepeatered links [5,6], it offers a broader bandwidth of operation [7] and improved noise performance compared to lumped amplification [2]. In particular, higher-order pumping can minimise the signal power variation (SPV) and reduce the effective attenuation by pushing the gain farther into the span [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The exponential increase of data traffic over the past decades has driven the development of multiple technologies capable of delivering higher capacities. However, as we approach the physical capacity limits of optical fiber, the need for higher optical-signal-to-noise (OSNR) requirements [1] becomes evident, and the current design of optical networks based on lumped amplification method (EDFA) will not be able to accommodate the less-noise resistant high level modulation formats required to handle the increased capacity needs in a single mode optical fibre [2]. Low noise distributed Raman amplification is now a well-established method that can overcome the limits set by EDFA and satisfy the bandwidth demand.…”
mentioning
confidence: 99%